Gallstones as a predictor of elevated cardiovascular disease risk: A meta-analysis and meta-regression of over 7.4 million participants - Refli Hasan; Fatemeh Allahbakhshi; Andrey D. Shlyk; Khadija Allahbakhshi (PLoS ONE, 2025)
Introduction Gallstone disease (GD) is a prevalent condition frequently encountered in surgical units worldwide. The objective of this comprehensive systematic review and meta-analysis study was to examine the relationship between gallstones and the risk of cardiovascular diseases (CVDs). Methods To conduct our study, we performed a systematic review and meta-analysis. We gathered relevant studies from reputable databases, including Web of Science, Scopus, PubMed, Cochrane, Google Scholar, and Embase. The quality of the articles was assessed using the Newcastle-Ottawa Scale checklist. To assess heterogeneity among the studies, we utilized statistical tests such as the Chi-square test, I² statistic, and forest plots. Meta-regression analysis considered variables such as the year of the study, study design, sample size, study quality assessment score, geographical region, average age of subjects, and follow-up duration. Additionally, we evaluated publication bias using Begg’s and Egger’s tests. Results Data from 22 studies conducted between 1985 and 2023 were analyzed. The combined number of participants across these studies was 7,496,303. The meta-analysis results revealed that individuals with GD had a higher risk of CVDs (Risk Ratio (RR): 1.29; 95% CI: 1.22–1.36; P <  0.001). Subgroup analysis showed consistent results across good quality studies (RR: 1.20, 95% CI: 11.12–1.28; P <  0.001), moderate quality studies (RR: 1.41, 95% CI: 1.15–1.74; P <  0.001), and low-quality studies (RR: 1.22, 95% CI: 1.15–1.30; P <  0.001). In the meta-regression analysis, none of the variables had a significant relationship with the observed heterogeneity (P-value > 0.10). In a sensitivity analysis, the estimated RR remained consistent, confirming the robustness of the meta-analysis results. Conclusion Our findings suggest an association between gallstone disease and an increased risk of CVDs. It seems that one of the important factors of this relationship is having common causes for the formation of gallstones and cardiovascular diseases. However, gallstones can be considered an important sign of increased risk of cardiovascular diseases.